Comparative Analysis of Looting Crimes: A Legal Perspective from Indonesia’s Positive Criminal Law and Islamic Criminal Law - Reza Fauzan,; Imam Yazid, (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
Looting is a serious criminal act that not only leads to material losses but also disrupts societal stability and security. This study aims to comparatively analyze the handling of looting crimes within Indonesia’s positive criminal law and Islamic criminal law to identify key differences and potential areas for legal integration. This research employs a qualitative approach with a normative juridical method, focusing on literature analysis, doctrinal studies, and relevant legal regulations. The study examines legal texts and interpretations to understand how looting is categorized and sanctioned within both legal frameworks. The findings indicate that under Indonesia’s positive criminal law, looting is classified as theft with violence under Article 365 of the Criminal Code (KUHP), with penalties in the form of imprisonment, adjusted based on the crime’s circumstances and impact. In contrast, Islamic criminal law categorizes looting as hirabah, a severe offense punishable by hudud sanctions, such as cross-amputation, to uphold maqasid shari’ah, ensuring the protection of religion, life, lineage, property, and intellect. The primary difference lies in the flexibility of sentencing in positive law versus the fixed and deterrent nature of Islamic law. This study provides a unique comparative perspective by analyzing both legal systems in the context of looting crimes. While existing research often examines these legal frameworks separately, this study explores their intersections and the potential for legal integration to enhance justice and crime prevention. The integration of Indonesia’s positive criminal law and Islamic criminal law could establish a more comprehensive, effective, and just legal framework for addressing looting crimes. By combining the proportional sentencing of positive law with the strong deterrence of Islamic law, policymakers may develop a more balanced approach to crime prevention and law enforcement.